Assessing Awareness of College Student Startup Entrepreneurs Toward Mass Entrepreneurship and Innovation From the Perspective of Educational Psychology - Liu, Mingji; Yu, Xingyang (Frontiers in Psychology, 2021)
Against the background of economic globalization, college student startup entrepreneurs’ awareness toward mass entrepreneurship and innovation is analyzed from the perspective of educational psychology, thus responding to national development strategies. First, the status quo of innovation and entrepreneurship education is understood using literature analysis. Second, the existing innovation and entrepreneurship education in colleges and universities is investigated with the QS (Questionnaire Survey) and interviews to discover the challenges that college students are facing during innovation and entrepreneurship. The QS results provide a data basis for subsequent strategies. Results demonstrate that 19.86% of the students have a complete understanding of innovation and entrepreneurship, while only 9.93% of the students are interested in innovation and entrepreneurship activities. The technical significance of innovation and entrepreneurship activities only accounts for 41.84%. Moreover, the vast majority of students (79.67%) believe that the curriculum of innovation and entrepreneurship education is single, simple, and irrelevant to their majors. Meanwhile, some problems have been found: for example, the teaching faculty is insufficient, and there is not a sound entrepreneurial atmosphere. As per the survey results, an innovation and entrepreneurship education strategy for core stakeholders, including universities, society, government, university teachers, and students, is formulated to promote the sound development of innovation and entrepreneurship education in colleges and universities. Besides, a training strategy in line with college students’ awareness toward mass entrepreneurship and innovation is formulated based on the current situation of innovation and entrepreneurship education, which can serve as a reference and has practical significance for enriching and perfecting innovation and entrepreneurship education system for college students.